2013
DOI: 10.1007/bf03356472
|View full text |Cite
|
Sign up to set email alerts
|

Development of target-site resistance (TSR) in Alopecurus myosuroides in Germany between 2004 and 2012

Abstract: Alopecurus myosuroides is one of the most important grass weeds on arable land in Germany. For many years, it has developed herbicide-resistant populations. ACCase-and ALS-inhibiting herbicides, in particular, have lost significant efficacy. Two different mechanisms are commonly known to confer resistance to herbicides: target-site resistance (TSR) and non-target-site resistance (NTSR). In Germany, only approximately 5 to 10% of the herbicide-resistant black-grass populations have been reported to show TSR so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…Data presented by Petersen and Rosenhauer (2014) demonstrated that resistance in Western Europe is mainly towards ACCase-inhibiting herbicides, while biotypes resistant to ALS-inhibiting herbicides are far less common. Many examples of A. myosuroides resistance to ACCase-inhibiting herbicides have been reported (Cocker et al 1999;Delye et al 2007;Rosenhauer et al 2013). In Poland, however, our study found no differentiation in the occurrence of A. myosuroides biotypes resistant to ALS-vs. ACCase-inhibiting herbicides ( Table 1).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Data presented by Petersen and Rosenhauer (2014) demonstrated that resistance in Western Europe is mainly towards ACCase-inhibiting herbicides, while biotypes resistant to ALS-inhibiting herbicides are far less common. Many examples of A. myosuroides resistance to ACCase-inhibiting herbicides have been reported (Cocker et al 1999;Delye et al 2007;Rosenhauer et al 2013). In Poland, however, our study found no differentiation in the occurrence of A. myosuroides biotypes resistant to ALS-vs. ACCase-inhibiting herbicides ( Table 1).…”
Section: Discussioncontrasting
confidence: 65%
“…In Western Europe, herbicide-resistant biotypes of A. myosuroides pose a great problem (Cavan et al 2000;Chauvel et al 2001;Price et al 2004;Rosenhauer et al 2013;Petersen and Rosenhauer 2014). Previously conducted studies have shown that A. myosuroides herbicide-resistant biotypes can also be found in Poland (Adamczewski et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any mutant ACCase or ALS isoforms currently known in A. myosuroides was verified by pyrosequencing, as described in Rosenhauer et al . (). Pyrosequencing was performed for the genotyping of alleles at seven positions that have been reported as substitutions conferring TSR to ACCase inhibitors in A. myosuroides .…”
Section: Methodsmentioning
confidence: 97%
“…These perceived risk values correspond to the current resistance situation in Germany, where a high resistance frequency has been reported for grass weeds such as Alopecurus myosuroides, Apera spica‐venti (L.) P. Beauv. and Lolium spp . There was a significant difference in the perceived resistance risk between farmers who had personal experience with resistant weeds on their farm (mean value of 8.2) and those who had not (mean value of 7.0; P < 0.001) with respect to the perceived resistance risk for grass weeds.…”
Section: Resultsmentioning
confidence: 90%
“…and Lolium spp. 15,16 There was a significant difference in the perceived resistance risk between farmers who had personal experience with resistant weeds on their farm (mean value of 8.2) and those who had not (mean value of 7.0; P < 0.001) with respect to the perceived resistance risk for grass weeds. This correlates with a significantly higher perceived resistance risk for wileyonlinelibrary.com/journal/ps grasses stated by farmers in the CMC (8.2; Table 7) compared with the RMC (6.8) and and the CRC (7,4) as the percentage of farmers with personal experience with resistant weeds on their farm was also highest in the CMC (Table 9).…”
Section: Resistance Experiences and Risk Perception Among Resistance mentioning
confidence: 96%